Freedom by Regulation: A Legal Assessment of the CRL Commission’s Report on the Commercialisation of Religion and Abuse of People’s Belief Systems : Research Article - Mapitsa, Cosmo (Religion & development, 2022)
The South African Commission for the Promotion and Protection of the Rights of Cultural, Religious and Linguistic Communities is one of the key institutions established by the Constitution of the country to strengthen its constitutional democracy. The Commission conducted investigations and released a report in 2017 related to suspicions that there are abuses of beliefs taking place in religious communities. The report was subjected to a number of challenges from academia, especially with regards to the constitutionality of some of the findings and recommendations of the Commission. In this article, it is argued that one of the contributing factors to the main shortcomings of the report emanates from a lack of nuance in the approach of the Commission. Considering the complex nature of religious beliefs, it is argued that the investigations by the CRL Rights Commission would have offered an opportunity for better conversation if the Commission had taken a human rights approach. In the main it is argued that a clear differentiation between the right to freedom of religion which vests on individuals, and the right of freedom of religious practice which vests on individuals in their capacity as members of religious communities, would have created a discourse that would better grapple with the complexity of ensuring maximum freedom of religion while creating safety for communal interests beyond specific beliefs.